Model Bisnis Kuliner Asinan dan Rujak Ciamix dengan Pendekatan Business Model Canvas (BMC) - Luthfia Qolbi Salima; Asep Mulyana; Wa Ode Zusnita Muizu (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The culinary industry continues to show promising growth along with increasing public demand for food products that are practical, fresh, and easily accessible. Micro, Small, and Medium Enterprises (MSMEs) play an important role in this sector, particularly in preserving and developing traditional culinary products. Asinan and Rujak Ciamix is a traditional culinary MSME that offers vegetable asinan, fruit asinan, and rujak made from fresh vegetables and fruits. This business has strong development potential because its products are in line with consumer preferences for fresh, practical foods with distinctive flavors. However, business development requires a structured understanding of the business model being implemented so that future development strategies can be formulated more clearly. This study aims to map the business model of Asinan and Rujak Ciamix using the Business Model Canvas approach. This research used a qualitative descriptive method, with data collected through interviews, observation, documentation, and relevant secondary sources. The data were analyzed through data collection, data reduction, data display, and conclusion drawing. The results show that Business Model Canvas mapping describes the business through nine interrelated elements, including product value, customer segments, sales channels, resources, activities, partners, revenue streams, and cost structure. The study implies that Business Model Canvas can help business owners understand their current business conditions and formulate a more focused, adaptive, and sustainable direction for business development.